Odpowiedź :
Odpowiedź:
a
4x= -6x
4x+6x=0
10x=0
x=0
b
6x-9x-3=18
-3x-3=18
-3x=18=3
-3x=21
x=-7
c
-6-4x=12x+48
-4x-12x=48+6
-16x = 54
x= -3 3\8
d tego podpunktu nie jestem pewna
3( 4x + 6)= 5(4-2x) + 60
12x+18=20-10x+60x
12x+18=20+50x
12x-50x=20-18
-38x=2
x=- 19
e
1\3x + 3\18= 1\2x |*18
6x+3=9x
6x-9x= -3
-3x= -3
x=1
licze na naj :)
Szczegółowe wyjaśnienie:
Odpowiedź:
a) 4x + 8 = 8 -6x
4x + 6x = 8 -8
10x = 0 /:10
x = 0
b) 6x - (9x + 3) = 18
6x -9x -3 = 18
-3x = 21 /:(-3)
x = -7
c) -6 -4x = 6(2x + 8)
-6 -4x = 12x + 48
-6 -48 = 12x + 4x
-54 = 16x /:16
- [tex]\frac{54}{16}[/tex][tex]\frac{}{}[/tex] = x
- 3[tex]\frac{6}{16}[/tex] = x
D i E nie wiem jak zrobić, przepraszam :(
Szczegółowe wyjaśnienie: